2014
DOI: 10.1007/978-3-319-14325-5_39
|View full text |Cite
|
Sign up to set email alerts
|

A Semantic-Based Approach to Attain Reproducibility of Computational Environments in Scientific Workflows: A Case Study

Abstract: Reproducible research in scientific workflows is often addressed by tracking the provenance of the produced results. While this approach allows inspecting intermediate and final results, improves understanding, and permits replaying a workflow execution, it does not ensure that the computational environment is available for subsequent executions to reproduce the experiment. In this work, we propose describing the resources involved in the execution of an experiment using a set of semantic vocabularies, so as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 16 publications
0
12
0
2
Order By: Relevance
“…Tools and ideas were presented, such as Pegasus [11] and Kameleon [5]: these tools target reproducible experiments, mainly addressing the problem exploiting virtual machines to reproduce the environment where an experiment is held. The main focus of these research groups keeps being on the virtual machine approach combined with cloud computing, as can be seen in [1] and [10]. More recent tools approach the reproducibility issue by building a workflow using web services or creating portable experimental software packages, like Taverna, VisTrails, Knime, Kepler and CDE.…”
Section: Infrastructure For Reproducible and Trusted Experimentsmentioning
confidence: 98%
“…Tools and ideas were presented, such as Pegasus [11] and Kameleon [5]: these tools target reproducible experiments, mainly addressing the problem exploiting virtual machines to reproduce the environment where an experiment is held. The main focus of these research groups keeps being on the virtual machine approach combined with cloud computing, as can be seen in [1] and [10]. More recent tools approach the reproducibility issue by building a workflow using web services or creating portable experimental software packages, like Taverna, VisTrails, Knime, Kepler and CDE.…”
Section: Infrastructure For Reproducible and Trusted Experimentsmentioning
confidence: 98%
“…A research study (Belhajjame et al, 2012) conducted to evaluate the reproducibility of scientific workflows has shown that around 80% of the workflows cannot be reproduced, and 12% of them are due to the lack of information about the execution environment (Santana-P´erez and P´erez-Hern´andez, 2014). This information affects a workflow execution in multiple ways.…”
Section: Motivationmentioning
confidence: 99%
“…In order to evaluate this aspect of workflow reproducibility, an algorithm has been proposed that compares the outputs produced by two given workflows. It uses the MD5 hashing algorithm [30] on the outputs and compares the hash value to verify the produced outputs. The MD5 algorithm outputs a string that is often used in many systems as the single data identifier, due to a small collision probability [31].…”
Section: B Workflow Output Comparisonmentioning
confidence: 99%